Metabolic kinetic modeling of [11C]methionine based on total-body PET in multiple myeloma - Li, Jiajin; Ni, Beiwen; Yu, Xiaofeng; Wang, Cheng; Li, Lianghua; Zhou, Yun; Gu, Yue; Huang, Gang; Hou, Jian; Liu, Jianjun; Chen, Yumei (European journal of nuclear medicine and molecular imaging, 2023)
Purpose Multiple myeloma (MM) is a malignant disease characterized by the secretion of monoclonal immunoglobulins and has a high demand for amino acids. [ 11 C]methionine total-body PET is capable of noninvasive dynamic monitoring of radiotracer in vivo, thus providing a way to reveal the dynamic changes of myeloma metabolism. This study aims to analyze the metabolic process of [ 11 C]methionine based on kinetic modeling, and to preliminary reveal its application value in MM. Methods Dynamic total-body [ 11 C]methionine PET/CT was conducted with uEXPLORER in 12 subjects (9 MM patients and 3 controls). The tissue time activity curves (TACs) of organs and bone marrows were extracted. Model fitting of TACs was operated using PMOD Kinetic Modeling. After validation by Goodness of fit (GOF), the reversible two-tissue compartment model (2T4k) was used to further analysis. R software was used to analyze the correlation between kinetic parameters and clinical indicators. Results The 2T4k has passed the criterion of GOF and was used to fit the data of 0-20 minutes. The [ 11 C]methionine net uptake rate (Ki) was significantly higher in the MM lesions than in the non-myeloma controls (control: 0.040±0.007 mL/g/min, MM: 0.171±0.108 mL/g/min, p=0.009). The Ki values were found to be correlated with M protein levels in MM patients. MM patients with t(4;14) translocations had an elevated k4 value compared with t(4;14) negative patients. Conclusion MM lesions have a propensity for uptake of [ 11 C]methionine. The serum levels of M protein are correlated with [ 11 C]methionine uptake rate in myeloma. Metabolic classification based on the k4 value may be a promising strategy for risk stratification in MM.